STRATEGI KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA ASN DI BIRO KESEJAHTERAAN RAKYAT SETDA PROVINSI SUMATERA BARAT - Arizona, Willia; Arif, Ernita; Azwar, Azwar (Jurnal Bilqolam Pendidikan Islam, 2024)
Organizational communication plays a crucial role in enhancing the performance of civil servants. This study aims to explore communication strategies at the Bureau of People's Welfare, Secretariat of the West Sumatra Provincial Government, and their impact on performance. The research employs a case study approach with interviews, observations, and document analysis. Results show that both formal and informal communication are essential for creating a productive work environment. However, challenges such as lack of openness and miscommunication persist. Recommendations include improving transparency and strengthening informal communication channels. The findings are expected to provide practical guidance for enhancing organizational communication strategies and overall performance of civil servants.